2013
DOI: 10.1002/poc.3146
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the rates of solvolysis of acetic p‐toluenesulfonic anhydride (acetyl p‐toluenesulfonate) and a comparison with acetyl halides

Abstract: The specific rates of solvolysis of acetyl p-toluenesulfonate have been measured by a rapid-response conductivity technique at temperatures in the temperature range of À10 to À55 C. For 13 solvents at À39.6 C, an extended Grunwald-Winstein equation correlation led to sensitivities to changes in solvent nucleophilicity of 0.56 and to changes in solvent ionizing power of 0.61. In 89.1% acetone at À20 C, the comparison with acetyl bromide solvolysis led to a k OTs / k Br ratio of 1.4. In methanol and methanol-d a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…A tabulation of literature values has been given. 9 For reactions indicated by extended Grunwald-Winstein treatments to have only moderate sensitivities to changes in solvent nucleophilicity (l values), lower k MeOH / k MeOD values are obtained, with a value of 1.29 for acetyl chloride. 43 For other aliphatic acyl chlorides, values in the range of 1.38 to 1.48 were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tabulation of literature values has been given. 9 For reactions indicated by extended Grunwald-Winstein treatments to have only moderate sensitivities to changes in solvent nucleophilicity (l values), lower k MeOH / k MeOD values are obtained, with a value of 1.29 for acetyl chloride. 43 For other aliphatic acyl chlorides, values in the range of 1.38 to 1.48 were observed.…”
Section: Resultsmentioning
confidence: 99%
“…9 Details of the conductivity apparatus and the computer procedure for calculation of the specific rates have previously been reported. 49,50 Since the variation of specific rates of solvolysis of 2 in aqueous acetone mixtures was considerably reduced from what had been observed for various acyl chlorides and chloroformate esters, we repeated the measurements, with new preparations of the mixed solvents and substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Initial objectives of the research reported here were as follows: (i) to test Eqn , using published data for alkyl, benzyl and benzoyl tosylates; (ii) to supplement recent Swain–Scott correlations relevant to the definition of N OTs (Eqn ), using new experimental data for solvolyses in higher alcohols. The correlations were then applied to the more complex solvolyses of carboxylic acid chlorides and sulfonates, taking advantage of insights obtained from recent data on solvolyses of mixed anhydrides and of acid chlorides in weakly nucleophilic media . Additional experimental data on kinetic solvent isotope effects (KSIE) were also obtained to help to identify the mechanistic change from S N 2 to S N 3.…”
Section: Introductionmentioning
confidence: 99%
“…1.7 in methanol [ 11 ], consistent with a third order mechanism ( Section 2.1 ). Other anhydrides show lower KSIE values: e.g., in methanol for acetyl tosylate (CH 3 COOTs, KSIE = 0.99 at −39.6 °C [ 50 ]), benzoyl tosylate (PhCOOTs, KSIE = 1.1 at −10 °C [ 11 ]), and other anhydrides (PhSO 2 ) 2 O, Ts 2 O, Ms 2 O) KSIE = 1.35–1.4 at −10 °C [ 51 , 52 ]); in mixed organic/water mixtures of 1.2–1.3 for solvolyses of various aromatic sulfonic acid anhydrides at 22.5 °C [ 53 ]. These results are consistent with changes within the S N 2-S N 1 spectrum.…”
Section: Resultsmentioning
confidence: 99%